Editorial: a new direction for ALT-J - Gráinne Conole (Association for Learning Technology, 2003)
The Association for Learning Technology celebrated its tenth anniversary this year and it can now be said that learning technology is a recognized research field, with a growing body of researchers and associated conferences and journals. Over the past two years as an editorial team we have undertaken a review of the position of ALT-J in relation to other journals in the area and considered the nature and scope of the papers we publish. We continue to expand our list of referees and have provided them with more detailed review forms to help guide them when considering recommendations on submissions and to encourage detailed, critical (and hopefully!) helpful feedback to authors. We would like to take this opportunity to thank all the referees for their involvement and commitment to the journal and for their continued work on refereeing papers. As part of the review process we will be moving to a new publisher, Taylor and Francis, commencing with Volume 12; this is, in part, driven by a desire to increase our international profile and readership, as well as seeking to have a better online presence including electronic access to all papers. We are, after all, a research journal on learning technologies! We are looking forward to taking the journal forward with Taylor and Francis but would also like to take this opportunity to thank our current publisher, University of Wales Press, for all their support and professional work over the years; it has been very good working with them.